ANTIOXIDANT NATURE OF ALLICIN TO CURE METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS. - J.VIMALIN HENA; RONIBALA NGANGOM (International Journal of Pharma and Bio Sciences, 2011)
Methicillin resistant Staphylococcus aureus (MRSA) continues to be one of the commonest pathogen encountered in clinical as well as laboratory practice. It has become a major health problem world wide. Newer antimicrobials/agents are urgently needed to combat this problem of MRSA resistance to various anti-staphylococcal agents. In the back drop of this difficult situation the main biological property of stabilized allicin (Diallyl thiosulfinate) and confirmed activity against MRSA is described. Allicin has been reported to have strong SH-modifying and antioxidant properties. The main antimicrobial effect of allicin may be due to its chemical reaction with thiol groups of various enzymes eg. alcohol dehydrogenase, thioredoxin reductase and RNA polymerase. In this study it was found that allicin is bactericidal against MRSA at concentrations of 130 to 138µg/ml.